Study on creep hardening-damage constitutive model of cemented tailings backfill based on time-harden theory - Yufan Feng; Guanghua Sun; Zhiyi Liu (PLoS ONE, 2025)
The wide application of the fill mining method is necessary for practicing the development concept of “green mountains are golden mountains” and protecting the surface landscape. In the underground quarry, the cemented tailings backfill (CTB) is mainly subjected to the gravity of the overlying rock layer in the mining area, which will cause creep problems in the long term. In order to protect the long-term stability of the mine surface, to study the creep hardening-damage characteristics of the CTB under the uniaxial action, for the maintenance age of 28d, cement-tailings ratios of 1:6 CTB to carry out uniaxial grading loading creep test, combined with the theory of time hardening Explore the creep process of the CTB in the hardening-damage law and the construction of the creep isomorphic model. The results show that the differences in the creep process of 1:6 cement-tailings ratios filler are caused by the joint existence of hardening and damage effects. In the stage of decelerated creep, creep hardening plays a major role; in the stage of stabilized creep, creep hardening and damage play a joint role; in the stage of accelerated creep, the creep damage effect is dominant; the strength of the CTB is strong and then weakened, and ultimately, the cumulative damage is too large to produce a “Y” type damage. The intrinsic model constructed based on the time-hardening theory better characterizes the creep of the 1:6 cement-tailings ratios of CTB under different stress levels. K and r are the material constants of the CTB, and the parameter K affects the time of decelerated creep during the decelerated creep stage, and the parameter r affects the creep rate of isokinetic creep.